Prevalence, risk factors, and outcomes associated with delayed second doses of antibiotics in sepsis at a large academic medical center - Meghan E. Cook; Brian R. Schuler; Michael J. Schontz; Kevin C. McLaughlin; Kenneth E. Lupi; Jeremy R. DeGrado; Chanu Rhee (Cambridge University Press, 2023)
Abstract Objective: To evaluate the prevalence, risk factors, and clinical impact of delays in second doses of antibiotics in patients with sepsis. Design: Single-center, retrospective, observational study. Setting: Large teaching hospital. Patients: Adult patients who triggered an electronic sepsis alert in the emergency department (ED), received ≥2 doses of vancomycin or an antipseudomonal beta-lactam, and were discharged with an ICD-10 sepsis code. Methods: We assessed the prevalence of delays in second doses of antibiotics by ≥25% of the recommended dose interval and conducted multivariate regression analyses to assess for risk factors for delays and in-hospital mortality. Results: The cohort included 449 patients, of whom 123 (27.4%) had delays in second doses. In-hospital death occurred in 31 patients (25.2%) in the delayed group and 71 (21.8%) in the non-delayed group (p = 0.44). On multivariate analysis, only location in a non-ED unit at the time second doses were due was associated with delays (OR 2.75, 95% CI 1.20-6.32). In the mortality model, significant risk factors included malignant tumor, respiratory infection, and elevated Sequential Organ Failure Assessment (SOFA) score but not delayed second antibiotic doses (OR 1.19, 95% CI 0.69-2.05). In a subgroup analysis, delayed second doses were associated with higher mortality in patients admitted to non-intensive care units (ICUs) (OR 4.10, 95% CI 1.32-12.79). Conclusions: Over a quarter of patients with sepsis experienced delays in second doses of antibiotics. Delays in second antibiotic doses were not associated with higher mortality overall, but an association was observed among patients admitted to non-ICUs.